A Simple Butterfly Lifecycle Algorithm for Measuring Company's Growth Performance. (August 2019) - Utama, D N; Mitchell, A; Fieri, B; Richard, H
Abstract: Five states of butterfly metamorphoses in its lifecycle naturally inspire algorithm creation. A simple butterfly lifecycle algorithm (BLCA) was successfully created by imitating a real butterfly lifecycle in five stages study; preliminary analysis, literature review, input-process-output analysis, logic analysis, and algorithm construction. The algorithm was represented thru activity diagram, pseudo-code, and class diagram. The dummy case of measuring company growth performance used to experimentally test the algorithm.